Caracterização de resíduos da indústria cerâmica e seu emprego em argamassas de cimento Portland. - Carvalho, Carlos Maviael de (2016)
Sustainable development drives companies to take steps to assist in minimizing the environmental impact. In the state of Paraiba there are about 140 red ceramic enterprises daily discarding lot of waste from failures of the production system. This type of waste is not easily reincorporated in nature, constituting a product which causes environmental impact. This research seeks to do the complete characterization of this material aimed at its use in mortar with Portland cement. The residue was collected in a partner industry and reduced through three different methods of fineness analysis, when it chose the most convenient. Then were made the chemical, mineralogical, physical characterization and pozzolanic activity by three methods: with lime; Portland cement; and the Chappelle modified method. They used two ceramic residues: blocks and roof tiles. The same time, were also featured two pozzolans used in local cement factories and two industrial metacaulins. The results indicated that the residue in the study did not deal with a very reactive pozzolan, because of the relatively low degree of amorphization, demonstrated by the Rietveld method. However, they performed well in the test pozzolanic activity with lime. The ceramic waste were then used as a cement replacement material in an industrialized mortar, at 0%; 10%; 15%, 20% and 25% content. Properties were obtained such as density, water retention, ultrasonic wave propagation velocity, dynamic modulus of elasticity and compressive strength at ages 7, 28 and 56 days, as well as to analyze water absorption by capillarity. The results showed the presence of ceramic wastes slightly interfere in the mortar properties, allowing to obtain loads close to the reference mortar with Portland cement economy. On day 56, all exceeded 5 MPa of resistance. In addition, a flowable mortar for flooring was developed. Made fluidity study of the paste, has come up to a 20% cement replacement content with good rheology and load higher than 20 MPa. Therefore, the industrial residue in question has strong potential application in mortars, and their use therein on a large scale can make the most ecologically clean business partner, setting an example for the local ceramist branch, and contribute to the sustainable development of the region.